Efektivitas latihan range of motion terhadap rentang gerak sendi jari kaki pada pasien stroke iskemik: A systematic review - Caryanto, Valerio Basuni Carlo; Saryono, Saryono; Trianto, Endang (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Ischemic stroke causes impaired motor function, including in the toes, which impacts patient mobility. One intervention to address this issue is Range of Motion (ROM) exercises. Purpose: To analyze the effectiveness of ROM exercises on toe joint range of motion in ischemic stroke patients. Method: This systematic review used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Articles were searched from Google Scholar, PubMed, and ScienceDirect databases, with the inclusion criteria being quantitative studies within the last 10 years. Seven articles were selected and critically analyzed using the JBI instrument. Results: The use of toe ROM exercise therapy devices has the potential to improve toe ROM and muscle strength in stroke patients. Based on the reviewed studies, passive and active ROM therapy have been shown to be effective in reducing joint stiffness, increasing flexibility, and strengthening muscles in patients with limited mobility. These devices are designed to provide consistent and programmed passive movements, thus being expected to be a more efficient substitute for manual therapy. Conclusion: Range of motion (ROM) exercises are a proven and recommended intervention in the rehabilitation of ischemic stroke patients to improve toe joint range of motion. Keywords: Ischemic Stroke; Range of Motion (ROM); Toe Joint Range of Motion. Pendahuluan: Stroke iskemik menyebabkan gangguan fungsi motorik termasuk pada jari kaki yang berdampak pada mobilitas pasien. Salah satu intervensi untuk mengatasi masalah ini adalah latihan Range of Motion (ROM). Tujuan: Untuk menganalisis efektivitas latihan ROM terhadap rentang gerak sendi jari kaki pada pasien stroke iskemik. Metode: Penelitian systematic review menggunakan panduan Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Pencarian artikel dari database Google Scholar, PubMed, dan ScienceDirect dengan kriteria inklusi yaitu studi kuantitatif 10 tahun terakhir. Sebanyak tujuh artikel terpilih dan dianalisis secara kritis menggunakan instrumen JBI. Hasil: Penggunaan alat Taromaki memiliki potensial untuk meningkatkan ROM dan kekuatan otot jari kaki pada pasien stroke. Berdasarkan studi yang telah diulas, terapi ROM pasif maupun aktif terbukti efektif dalam menguranggi kekakuan sendi, meningkatkat fleksibelitas, dan memperkuat otot pada pasien dengan keterbatasan mobilitas. Alat tersebut dirancang untuk memberikan gerakan pasif terprogram yang konsisten, sehingga diharapkan mampu menggantikan terapi manual secara lebih efisien. Simpulan: Latihan ROM merupakan intervensi yang terbukti efektif dan direkomendasikan dalam rehabilitasi pasien stroke iskemik untuk meningkatkan rentang gerak sendi jari kaki. Kata Kunci: Range of Motion (ROM); Rentang Gerak Sendi Jari Kaki; Stroke Iskemik.